2018
DOI: 10.3233/jad-180361
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Supplementation in the Diet Reduces Oxidative Damage and Improves Antioxidant Status in Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Our previous study has shown beneficial effects of walnuts on memory and learning skills in transgenic mouse model of Alzheimer’s disease (AD-tg). To understand underlying mechanism, we studied here whether walnuts can reduce oxidative stress in AD. From 4 months of age, experimental AD-tg mice were fed diets containing 6% (T6) or 9% walnuts (T9) (equivalent to 1 or 1.5 oz, of walnuts per day in humans) for 5, 10, or 15 months. The control groups, i.e., AD-tg (T0) and wild-type (Wt) mice, were fed diets withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
4
21
0
Order By: Relevance
“…The metabolism of lipid peroxides produces MDA, indirectly reflecting the severity of free radical attack by. Consistent with previous results [33], we found that the concentration of MDA was significantly increased in N2a-APPsw cells. However, it was significantly decreased by EGb treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The metabolism of lipid peroxides produces MDA, indirectly reflecting the severity of free radical attack by. Consistent with previous results [33], we found that the concentration of MDA was significantly increased in N2a-APPsw cells. However, it was significantly decreased by EGb treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Transgenic mice fed diets containing walnuts exhibited significantly reduced oxidative stress, as demonstrated by decreased levels of ROS, lipid peroxidation, and protein oxidation and enhanced activities of anti-oxidant enzymes compared with those in the control diet mice. Long-term supplementation with walnuts was more effective in reducing oxidative stress in this animal model [78]. These observations indicate that walnut can reduce oxidative stress, not only by scavenging free radicals, but also by maintaining the anti-oxidant status.…”
Section: Effects Of Walnut On Lipotoxicity (Oxidative Stress)supporting
confidence: 58%
“…Oxidative stress was observed to be significantly reduced in AD-tg mice on diets with 6% (T6) or 9% walnuts (T9), as shown by lower levels of ROS, decreased lipid peroxidation and protein oxidation, and significant improvement in activities of antioxidant enzymes in these mice compared to control T0 mice. Long-term supplementation with walnuts in the diet for 10 or 15 months was found to be more effective in reducing ROS levels and oxidative damage to lipids and proteins and in improving antioxidant status in comparison with short-term supplementation with walnuts for 5 months in AD-tg mice [37].…”
Section: Walnuts Decrease Aβ-induced Oxidative Stress and Cell Damagementioning
confidence: 93%
“…To further understand the mechanisms underlying the beneficial effects of dietary supplementation with walnuts in AD, we recently studied whether short-or long-term supplementation with walnuts in the diet can reduce oxidative damage and/or enhance antioxidant defense in AD-tg mice [37]. AD-tg mice consuming a control diet without walnuts (T0) showed a significant age-dependent increase in ROS levels, lipid peroxidation, and protein oxidation, which was coupled with decreased activities of antioxidant enzymes (superoxide dismutase, catalase) compared to wild-type mice on the control diet.…”
Section: Walnuts Decrease Aβ-induced Oxidative Stress and Cell Damagementioning
confidence: 99%